Alarmins and Their Receptors as Modulators and Indicators of Alloimmune Responses. Issue 2 (12th July 2016) - Matta, B. M.; Reichenbach, D. K.; Blazar, B. R.; Turnquist, H. R.
Abstract : Cell damage and death releases alarmins, self‐derived immunomodulatory molecules that recruit and activate the immune system. Unfortunately, numerous processes critical to the transplantation of allogeneic materials result in the destruction of donor and recipient cells and may trigger alarmin release. Alarmins, often described as damage‐associated molecular patterns, together with exogenous pathogen‐associated molecular patterns, are potent orchestrators of immune responses; however, the precise role that alarmins play in alloimmune responses remains relatively undefined. We examined evolving concepts regarding how alarmins affect solid organ and allogeneic hematopoietic cell transplantation outcomes and the mechanisms by which self molecules are released. We describe how, once released, alarmins may act alone or in conjunction with nonself materials to contribute to cytokine networks controlling alloimmune responses and their intensity. It is becoming recognized that this class of molecules has pleotropic functions, and certain alarmins can promote both inflammatory and regulatory responses in transplant models. Emerging evidence indicates that alarmins and their receptors may be promising transplantation biomarkers. Developing the therapeutic ability to support alarmin regulatory mechanisms and the predictive value of alarmin pathway biomarkers for early intervention may provide opportunities to benefit graft recipients. Abstract : Released alarmins, or self‐derived immunomodulatory molecules, can detect allograft rejection and are emerging as pleotropic molecules that augment inflammatory immune responses, but also support immune regulation and tissue repair.